The Impact of Merger Bids on the Participating Firms' Security Holders - ASQUITH, PAUL; KIM, E. HAN (Journal of Finance, 1982)
ABSTRACT This paper investigates whether merger bids have an impact on the wealth of the participating firms' bondholders and stockholders. Monthly and daily bond and stock returns are calculated relative to the announcement date of a merger bid for a sample of conglomerate mergers. The results show that while the stockholders of target firms gain from a merger bid, no other securityholders either gain or lose. To provide direct evidence on the existence of “diversification effects” and “incentive effects,” we test whether the bondholders' returns are dependent upon the correlation between the returns of the merging firms and whether the size of the bondholders' and stockholders' returns in individual mergers are correlated. The results are consistent with a capital market that efficiently resolves conflicts of interest between stockholders and bondholders.